Inverse changes in plasma tetranectin and titin levels in patients with type 2 diabetes mellitus: a potential predictor of acute myocardial infarction? - Rahim, Mohd Aizat Abdul; Rahim, Zubaidah Haji Abdul; Ahmad, Wan Azman Wan; Bakri, Marina Mohd; Ismail, Muhammad Dzafir; Hashim, Onn Haji (Springer Nature, 2018)
An early intervention using biomarkers to predict acute myocardial infarction (AMI) will effectively reduce global heart attack incidence, particularly among high-risk patients with type 2 diabetes mellitus (T2DM). This study attempted to identify potential biomarkers by detecting changes in the levels of plasma proteins in T2DM patients following onset of AMI in comparison with those without AMI. Volunteer T2DM patients without AMI (control; n=10) and T2DM patients with AMI (n=10) were recruited. Plasma samples from these patients were evaluated via two-dimensional gel electrophoresis (2DE) to screen for proteins with level changes between the two groups. The abundance of spots on gel images was analyzed using Progenesis SameSpots and subjected to false discovery rate (FDR) analysis. Protein spots with statistically significant changes of at least 1.5 fold were selected for mass spectrometry (MS) analysis. Due to strong cardiac connections, tetranectin and titin were evaluated by enzymelinked immunosorbent assay (ELISA). The adjusted P-values and fold changes between the two groups resulted in identification of 34 protein spots with significantly altered abundance. Upon MS analysis, 17 plasma proteins were identified: tetranectin, titin, clusterin, haptoglobin, myosin-13, zinc fnger protein 445, DNA repair protein RAD50, serum albumin, apolipoprotein A-IV, caspase-6, aminoacyl tRNA synthase complex-interacting multifunctional protein 1, serotransferrin, retinol-binding protein 4, transthyretin, alpha-1-antitrypsin, apolipoprotein A-I and serum amyloid A. Comparable patterns of changes in tetranectin and titin between the control and AMI groups were confirmed using ELISA. In summary, tetranectin and titin in plasma appeared to be closely associated with the onset of AMI among T2DM patients and can be used as potential biomarkers for prediction of a cardiac event, though this requires validation in a prospective cohort study.